Comprehensive Molecular Analyses of a Macrophage-Related Gene Signature With Regard to Prognosis, Immune Features, and Biomarkers for Immunotherapy in Hepatocellular Carcinoma Based on WGCNA and the LASSO Algorithm - Wang, Tao; Dai, Liqun; Shen, Shu; Yang, Yi; Yang, Ming; Yang, Xianwei; Qiu, Yiwen; Wang, Wentao (Frontiers in Immunology, 2022)
Macrophages has been reported to exert a crucial role in hepatocellular carcinoma (HCC). Herein, our study was aimed to explore the macrophage-related genes and established macrophage-related signature (MRS) model to predict the overall survival (OS) of patients with HCC based on these genes. We screened the macrophage-related gene module by weighted gene co-expression network analysis (WGCNA), the Least Absolute Shrinkage and Selection Operator (LASSO) Cox regression analysis was utilized for further selection, and the selected genes were entered into stepwise regression to develop the MRS model, which was further validated in Gene Expression Omnibus (GEO) and the International Cancer Genome Consortium (ICGC) datasets. We analyzed the biological phenotypes associated with macrophages in terms of functional enrichment, tumor immune signature and tumor mutational signature. The patient’s response to immunotherapy is inferred by the tumor immune dysfunction and exclusion (TIDE) score, the immunophenotype score (IPS) and the IMvigor210 dataset. A novel MRS model was established based on the LASSO regression coefficients of PON1, IL15RA, NEIL3, HILPDA, PFN2, HAVCR1, ANXA10, CDCA8, EPO, S100A9, TTK, KLRB1, SPP1, STC2, CYP26B1, GPC1, G6PD and CBX2. No matter in which dataset, MRS has been identified as an independent risk factor affecting poor OS in HCC patients. Additionally, our research indicated that high risk score of MRS model was significantly related to tumor staging, pathological grade, the tumor-node-metastasis (TNM) stage and survival. Several genes of the human leukocyte antigen (HLA) family and immune checkpoints were highly expressed in the high-risk group. In addition, the frequency of tumor mutations is also higher in the high-risk group. According to our analyses, the higher risk score of the MRS model may respond better to immunotherapy.